Relationship between pulmonary function, maximum inspiratory pressure, oxygen saturation and exercise capacity in patients with chronic obstructive pulmonary (Research, Society and Development, 2022)
Introduction: Exercise capacity is one of the determining factors in the prognosis of patients with COPD. Assessing exercise capacity and its relationships can contribute to understanding the factors that impact the reduction of physical activity and provide subsidies to mitigate its deleterious effects. Objective: The purpose of this study was to assess the relationship between pulmonary function, respiratory muscle strength, baseline peripheral oxygen saturation and exercise capacity. Methodology: 11 individuals diagnosed with COPD were selected for this study (5 patients in GOLD Stage 3-4; 6 patients in GOLD stage 1-2), of both genders, with a mean age of 70.73±6.19 years. All patients underwent evaluation of the distance covered in the six-minute walk test (6MWD), pulmonary function (FEV1%pred, FVC%pred e %FEV1/FVC), respiratory muscle strength (MIP, MEP) and baseline peripheral oxygen saturation (baseline SpO2). Results: The results showed a positive correlation between baseline SpO2 (p=0.007), FVC%pred (p=0.02) and the 6MWD. Conclusions: The results of this study allow us to infer that there is an association between 6MWD, baseline pulse oxygen saturation, FVC and gender. Thus, this study suggests that the lower oxygenation at rest is correlated with a worsening of lung function and lower tolerance of the individual to physical exercise.